2013
DOI: 10.1142/s0218194013500137
|View full text |Cite
|
Sign up to set email alerts
|

Development of Scientific Software: A Systematic Mapping, a Bibliometrics Study, and a Paper Repository

Abstract: Scientific and engineering research is heavily dependent on effective development and use of software artifacts. Many of these artifacts are produced by the scientists themselves, rather than by trained software engineers. To address the challenges in this area, a research community often referred to as "Development of Scientific Software" has emerged in the last few decades. As this research area has matured, there has been a sharp increase in the number of papers and results made available, and it has thus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Bibliometric rankings are quite common in field of SE, e.g., Caia and Card (2008), Wohlin (2007Wohlin ( , 2008, Glass and Chen (2001, 2003, Tse et al (2006), Wong et al (2008Wong et al ( , 2009Wong et al ( , 2011, Ren and Taylor (2007), Garousi and Varma (2010), , McCain et al (2005), Parnas (2007), Meyer et al (2009), Geist et al (1996, Farhoodi et al (2013), Garousi and Ruhe (2013), Jia and Harman (2010), Harman et al (2009). We discuss these works in the following.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Bibliometric rankings are quite common in field of SE, e.g., Caia and Card (2008), Wohlin (2007Wohlin ( , 2008, Glass and Chen (2001, 2003, Tse et al (2006), Wong et al (2008Wong et al ( , 2009Wong et al ( , 2011, Ren and Taylor (2007), Garousi and Varma (2010), , McCain et al (2005), Parnas (2007), Meyer et al (2009), Geist et al (1996, Farhoodi et al (2013), Garousi and Ruhe (2013), Jia and Harman (2010), Harman et al (2009). We discuss these works in the following.…”
Section: Related Workmentioning
confidence: 99%
“…We have also been able to find several systematic mapping and systematic literature review (SLR) studies, e.g., Farhoodi et al (2013), Jia and Harman (2010), Harman et al (2009) which, as part of their studies, have conducted a bibliometric assessment of papers in focused sub-areas of SE, namely: development of scientific software (Farhoodi et al 2013), software mutation testing (Jia and Harman 2010), and search-based SE (Harman et al 2009). These studies have measured and reported the number of publications by each country in these areas and provided interesting trends and insights.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations